A Strategy for the Development of Instructors’ Professionalism in Thai Private Universities - Islam, Mohammad Ariful; Asavisanu, Poonpilas; Merritt, Matthew Reed (Scholar: Human Sciences, 2021)
This study aimed to develop a strategy for the development of instructors’ professionalism in Thai private universities. The study was based on the following research objectives: 1) To explore the desired components that constitute instructors’ professionalism in Thai private universities, 2) To examine the current level of instructors’ professionalism in Thai private universities, 3) To determine the components that impact the development of professionalism for instructors’ professionalism in Thai private universities, and 4) To propose a strategy for the development of instructors’ professionalism in Thai private universities. The methods applied during the study included content analysis, questionnaires, semi-structured interviews, and a focus group. Participants in the study were 364 instructors and administrative staff from ten Thai private universities. Content analysis, descriptive statistics, multiple regression, and correlational analysis were used to analyze the data. The desired components that constitute instructor professionalism obtained from the content analysis and expert interviews were: Content Knowledge, Instructional Knowledge, Self-Efficacy and Self-Confidence, Ethics and Care, and Transformational Leadership. The current overall level of instructors’ professionalism was high. The multiple regression analysis found that four variables were statistically significant at the .01 level of confidence: Self-Efficacy and Self-Confidence, Instructional Knowledge, Content Knowledge, and Ethics and Care, p<.01, R2 = .525. From this data, a strategy was developed as a recommendation for the enhancement of professionalism for instructors at Thai private universities.